Ring-Opening Metathesis Polymerization and Hydrogenation of Ethyl-substituted Tetracyclododecene - Kwon, Oh Joon; Huyen Thanh Vo; Lee, Sul Bee; Kim, Tae Kyung; Kim, Hoon Sik; Lee, Hyunjoo (KOREAN CHEMICAL SOC, 2011)
Ring-opening metathesis polymerization (ROMP) of an ethyl-substituted tetracyclododecene (8-ethyl-tetracyclo[4.4.0.1(2,5).1(7,10)] dodec-3-ene, Et-TCD) was carried out in the presence of a ternary catalyst system consisting of WCl(6), triisobutyl aluminium (iso-Bu(3)Al), and ethanol. The optimal molar ratio of Et-TCD/WCl(3)/iso-Bu(3)Al/ethanol was found as 500/1/3/2 at which the yield of ring-opened polymer was 100%. I-Hexene was shown to be an effective molecular weight controlling agent for ROMP reaction of Et-TCD. The hydrogenation of the ring opened polymer (p-Et-TCD) was conducted successfully using Pd(5 wt %)/gamma-Al(2)O(3) at 80 degrees C for 1 h. Chemical structures of p-Et-TCD and its hydrogenated product(H(2)-p-Et-TCD) were characterized using 2D NMR techniques ((1)H-(1)H COSY and (1)H-(13)C HSQC). The changes of physical properties such as thermal stability, glass transition temperature and light transmittance after the hydrogenation were also investigated using TGA, DSC, and UV.
Keywords: ATACTIC POLYMER; COPOLYMERS; CATALYST; ROMP; POLY(ENDO-DICYCLOPENTADIENE); DERIVATIVES; COMPLEXES